Determination of energy-level alignment in molecular tunnel junctions by transport and spectroscopy: self-consistency for the case of oligophenylene thiols and dithiols on Ag, Au, and Pt electrodes - Xie, Zuoti; Bâldea, Ioan; Frisbie, C. Daniel (Journal of the American Chemical Society, 2019)
We report detailed measurements of transport and electronic properties of molecular tunnel junctions based on self-assembled monolayers (SAMs) of oligophenylene monothiols (OPTn, n = 1-3) and dithiols (OPDn, n = 1-3) on Ag, Au, and Pt electrodes. The junctions were fabricated with the conducting probe atomic force microscope (CP-AFM) platform. Fitting of the current-voltage (I-V) characteristics for OPTn and OPDn junctions to the analytical single-level tunneling model allows extraction of both the HOMO-to-Fermi-level offset (εh) and the average molecule-electrode coupling (Γ) as a function of molecular length (n) and electrode work function (Φ). Significantly, direct measurements of εhUPS by ultraviolet photoelectron spectroscopy (UPS) for OPTn and OPDn SAMs on Ag, Au, and Pt agree remarkably well with the transport estimates εhtrans, providing strong support—beyond the high quality I-V simulations—for the relevance of the analytical single-level model to simple molecular tunnel junctions. Because the UPS measurements involve SAMs bonded to only one metal contact, the correspondence of εhUPS and εhtrans also indicates that the top contact has a weak effect on the HOMO energy. Corroborating ab initio calculations definitively rule out a dominant contribution of image charge effects to the magnitude of εh. Thus, the effective molecular tunnel barrier εh is determined, and essentially pinned, by the formation of a single metal-S covalent bond per OPTn or OPDn molecule.
Gesehen am 08.07.2019